2015
DOI: 10.7314/apjcp.2014.15.24.10763
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Inadequate Bowel Preparation before Elective Colonoscopy in Thai Patients

Abstract: Background: The incidence of inadequate bowel preparation before elective colonoscopy in this region has never been studied. Materials and Methods: The authors prospectively described the incidence and factors related to inadequate bowel preparation in Thammasat university hospital. Bowel preparation quality was accessed by using Aronchick scale. Factors associated with inadequate bowel preparation were also recorded. Results: Two hundred patients undergoing elective outpatient colonoscopy were enrolled. Inade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…Bhanthumkomol et al . also found that incomplete preparation (OR 7.7, 95% CI 1.62–36.64) and dietary intake of vegetables before colonoscopy (OR 3.26, 95% CI 1.14–9.28) were associated with poor bowel cleaning …”
Section: Discussionmentioning
confidence: 85%
“…Bhanthumkomol et al . also found that incomplete preparation (OR 7.7, 95% CI 1.62–36.64) and dietary intake of vegetables before colonoscopy (OR 3.26, 95% CI 1.14–9.28) were associated with poor bowel cleaning …”
Section: Discussionmentioning
confidence: 85%
“…[ 6 ] Previous reports indicate that several factors are associated with inadequate colonoscopy bowel preparation including advanced age, male sex, education level, constipation, history of abdominal surgery, stroke, dementia, treatment with psychotropic drugs, and non-compliance with preparation instructions. [ 7 8 9 ] However, few studies have investigated the rate of and risk factors for inadequate bowel preparation in the elderly. Additionally, existing studies were almost exclusively conducted in Western countries, and bowel preparation has rarely been investigated in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Logistic regression was used to conduct subgroup analyses of the primary end‐point for each of five potential risk factors for suboptimal BP: regular opioid use, history of diabetes, regular use of laxatives, polypharmacy (use of more than eight regular medications), and poor mobility . Wald χ 2 tests were used to investigate the main effects of the subgroup factor and the treatment and also their two‐way interaction.…”
Section: Methodsmentioning
confidence: 99%